Analysis of Students' Beginning Reading Ability in Phase A at Madrasah Ibtidaiyah - Mastoah, Imas; Fauziah, Ismi; Inayah, Inayah; Amilhasan, Zaid Ladja (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Students' skills in beginning reading are a determining indicator for developing further reading skills, many elementary school students still experience difficulties in beginning reading. This study aims to analyze the reading skills of grade 1 students at MI Ats-Tsauroh. This research used qualitative methods. Data was collected through observation, reading test activities to grade 1 and 2 students of MI Ats-Tsauroh, and interviews with grade 1 and 2 teachers. The data that has been collected is then analyzed in depth regarding the reading ability of phase A students. The results showed that 62% of students could read, indicating that most students have developed basic reading skills. However, 38% of students still cannot read fluently, suggesting that many students may need additional support in their reading development. Then, 70% of students can read independently, which shows that most students have good independent reading skills. However, 30% of students are not fully fluent in independent reading. Internal factors in independent reading obstacles include low student motivation, low intelligence, and poor learning motivation. External factors include the surrounding environment, less supportive parents, and teacher limitations in reaching all students in learning. Therefore, additional efforts are needed from schools, teachers, and parents to improve students' reading skills more evenly.